Identification and Prioritization of Components for Measuring Cultural Sustainability in Urban Areas through Meta-Synthesis Method - Seyed Hadi hosseini; omid gholami (مطالعات جغرافیایی مناطق خشک)
Aim: This research aims to deepen the understanding of the role of culture in the sustainability of urban environments, particularly by identifying and introducing the key components and indicators essential for evaluating cultural sustainability in cities Material & Method: The meta-synthesis method has been used to identify and extract the components and indicators of cultural sustainability in urban areas. Finding: The research findings indicate that the primary components for measuring cultural sustainability can be categorized into 12 key components: cultural identity, cultural infrastructure, cultural discourse and interactions, cultural heritage, cultural diversity, cultural vitality, cultural participation, cultural capital, cultural governance, cultural economy, cultural resilience, and sense of place. Among these 12 identified components, 11 are common in both Persian and English literature, with only one distinction: cultural discourse and interactions in Persian literature versus cultural resilience in English literature. The prioritization of the identified components reveals that, in Persian texts, the three highest-priority components are cultural identity, cultural infrastructure, and cultural diversity. In contrast, the three prioritized components in English texts are cultural identity, cultural heritage, and cultural economy. The components with the least representation are cultural participation and cultural capital in Persian literature, as well as cultural participation and resilience in English literature. Conclusion: Given the existing gaps in measuring cultural sustainability in urban areas and the minimal number of studies conducted, there is a pressing need for further theoretical and empirical research to establish objective indicators for assessing cultural sustainability and to evaluate the reliability and validity of measurement tools. Innovation: The most significant innovative and practical aspect of this research is that a comprehensive study addressing the identification of cultural sustainability components based on a meta-synthesis method and reviewing over 40 domestic and international studies has not yet been conducted.